Sexual and reproductive health services for autistic young people in the United States: A conceptual model of utilization. Issue 1 (7th February 2023) - Holmes, Laura Graham; Anderson, Kristy; Sieber, Greg S.; Shattuck, Paul T.
Abstract: Background: Sexual and reproductive health services promote the ability of people to have safe, satisfying, non‐coercive sexual experiences and make informed decisions about pregnancy. Stakeholder input is needed to understand barriers or facilitators to service access for autistic people, who report unmet needs. Methods: We recruited 18 autistic people, 15 parents, and 15 service providers in the United States to participate in an interview and two surveys. Using their input, we created a conceptual model of sexual and reproductive health service needs, access barriers, and facilitators. Results: Stakeholders rated a variety of sexual and reproductive health services as important for autistic people, including those with intellectual disability or minimal verbal language. Stakeholders identified barriers to sexual and reproductive health service utilization including lack of service availability, lack of service providers with autism or neurodiversity training, lack of accurate information about autism and sexuality, verbal and communication differences that are not accommodated by service providers, and socio‐cultural attitudes about sexuality. Stakeholders identified facilitators to service access including person‐centered, trauma‐informed care, service accommodations such as clear and detailed expectations, and long‐enough appointments. We created a conceptual model based on the social ecological model of health to organize these utilization factors and support future research, provider, and policy action. Stakeholders provided feedback and responded favorably on the model's accuracy, utility for spurring research, practice, and policy improvements, and application to diverse groups of autistic people. Conclusions: The model shows the many feasible ways to support equitable access to services for autistic people.